Identifikasi Tingkat Kekumuhan Pada Kabupaten Langkat Dengan Metode AHP (Analytical Hierarcy Process) - Yunita Syafitri Rambe (Universitas Sebelas Maret Surakarta, 2021)
Problems that occur in an urban level of uneven service facilities and infrastructure especially in the urban suburbs. This is also the case in Langkat Regency. The existence of these settlements is classified into squatters or slums that grow unplanned on unlicensed state land. The purpose of the research is to identify the slums, using the AHP method, starting from the collection of primary and secondary data, field observations, interviews, and documentation, which are then assessed against the criteria that have been set. The final result of the weighting resulted in the classification of the level of slums in the village. It is hoped that the results of this study can be useful for other research.